Understanding green supply chain information integration on supply chain process ambidexterity: The mediator of dynamic ability and the moderator of leaders’ networking ability - Lyu, Tu; Guo, Yulin; Lin, Huan (Frontiers in Psychology, 2022)
Based on dynamic capability theory, this paper aims to explore the influence of green supply chain information integration (IT system integration and information sharing) on supply chain process ambidexterity (efficiency and flexibility) and expounds on the mediation mechanisms (supply chain dynamic capability) and the boundary condition (network structure capability) between the two. Through the sample data test research model of 351 managers of manufacturing enterprises, it is found that IT system integration can effectively promote the information sharing level of green supply chain enterprises. Supply chain dynamic capability partially mediates the influence of IT system integration and information sharing on supply chain process ambidexterity. Moreover, network structure capability positively moderates the relationship between absorptive capacity, innovation capacity, and supply chain process ambidexterity, but does not play a significant role in the relationship between adaptive capacity and supply chain process ambidexterity.